Christ is risen a three-part choir with string orchestration and piano accompaniment easter cantata for the Junior Youth Choir of Bethany Baptist Church, Cubao - Galano, Kimberly Mae A.
The project is an action research that focuses on teaching the newly formed Bethany Baptist Church Cubao, Junior Youth Choir (JY) on how to properly sing as a chorale. It includes practice plans, vocalises, and three-part (SAT) arrangements, accompanied and a capella, of church hymns for an Easter Cantata. It focuses on helping the adolescents during the transition stage and is of great help especially for those churches that do not have a youth choir and want to start one.